DISTRIBUTION, STATUS AND CONSERVATION OF REPTILIAN FAUNA IN THE COASTAL AREAS OF KARACHI WITH SPECIAL REFERENCE TO MARINE TURTLES - U. Manzoor; M. Z. Khan; M. A. Iqbal (Journal of Animal and Plant Sciences, 2019)
During the period from 2014 to 2017, distribution, status and conservation of reptilian fauna in the coastal areas of Karachi with special reference to marine turtles have been studied. In this study only Green turtle (Chelonia mydas) has been recorded from the selected study areas viz. Sandspit, Hawkesbay and Cape Monze. Nine species of lizards viz. Common tree lizard (Calotes versicolor versicolor),Spotted barn gecko(Hemidactylus brookii),Yellow bellycommon house gecko (Hemidactylus flaviviridis),Persian house gecko (Hemidactylus persicus), Blotched house gecko (Hemidactylus triedrus),Mediterranean house gecko (Hemidactylus  turcicus),Blue tail sand lizard (Acanthodactylus cantoris), Spotted lacerta (Mesalina watsonana) and Bengal monitor(Varanus bengalensis) were recorded from Sandspit, Hawkesbay and Cape Monze. Five species of Sea snakes viz. Blotched diadem snake (Sphalerosophis diadema diadema), Blue green sea snake (Hydrophis caerulescens), Annulated sea snake (Hydrophis cyanocinctus), Yellow sea snake (Hydrophis spiralis)and Spotted small headed sea snake (Microcephalophis cantoris) were recorded from Sandspit, Hawkesbay and Cape Monze. Two species of terrestrial snakes viz. Cliff racer (Platyceps rhodorachis) and Saw scaled viper (Echis carinatus) were also recorded from Karachi coast. The population of reptilian species at Karachi coast is declining due to disturbance by anthropogenic activities, construction and developmental activities on beach front land, inappropriate management and fishing activities.
Keywords: Karachi coast; reptilian fauna; nesting; distribution; status